2019
DOI: 10.1364/oe.27.001090
|View full text |Cite
|
Sign up to set email alerts
|

Raman imaging through multimode sapphire fiber

Abstract: We report on a sapphire fiber Raman imaging probe's use for challenging applications where access is severely restricted. Small-dimension Raman probes have been developed previously for various clinical applications because they show great capability for diagnosing disease states in bodily fluids, cells, and tissues. However, applications of these sub-millimeter diameter Raman probes were constrained by two factors: first, it is difficult to incorporate filters and focusing optics at such small scale; second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The far-field modality can thus be used to guide the insertion of the probe while providing organ-or tissue-scale imagery, which can then be promptly converted into an instrument imaging at the subcellular scale. Combined with spectroscopic imaging methods [30][31][32], the technology has potential for in situ diagnostics at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…The far-field modality can thus be used to guide the insertion of the probe while providing organ-or tissue-scale imagery, which can then be promptly converted into an instrument imaging at the subcellular scale. Combined with spectroscopic imaging methods [30][31][32], the technology has potential for in situ diagnostics at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…In Section 5.5, we have shown that sapphire has much weaker and narrower Raman peaks. Such Raman background with high transparency provides a clean spectrum and high imaging quality, [ 194 ] with the system illustrated in Figure . A sapphire fiber (Micromaterials, Inc. 5 cm long with 60 µm core) is used to deliver the excitation laser and collect the Raman scattering from the sample simultaneously.…”
Section: Applicationsmentioning
confidence: 99%
“…However, the fibre material itself, commonly silica, produces a Raman signal as the pump light propagates along it (referred to as the fibre background, FB) which can be several orders of magnitude greater than the tissue Raman signal. Recent advances in fibre manufacturing have opened up new avenues to address this; notably, non-standard fibre materials such as sapphire [28] and microstructured, hollow-core fibres [29,30] have been shown to dramatically reduce the fibre background signal. Single-fibre probes still exhibit limited collection efficiency and so instead multicore fibres or fibre bundles are sometimes used to improve signal collection without increasing the complexity of manufacture significantly [31,32].…”
Section: Raman Probe State Of the Artmentioning
confidence: 99%